Análise experimental de pilares de concreto armado submetidos à flexo-compressão, reforçados com concreto auto-adensável e conectores - NASCIMENTO, Poliana Paula (2009)
Many problems involving cases of ruins of buildings, bridges, etc., specifically ruin of columns, which are among the most important links in the whole structure, due to project flaw, bad execution or even for the evolution and changing habits. Therefore it has been of fundamental importance researches on the experimental behavior of structures. When conducting a strengthening column using dry with increased self-compacting concrete, it has the drawback of a sudden rupture by peeling the reinforcement. For this, there is a need to study the area of adhesion between substrate and to strengthen and create a way of preparation of this interface area so that the column increases may come into ruin in a ductile flexural as well as in a monolithic column. Thus, it s been developed an experimental study in the School of Civil Engineering, Federal University of Goias, based on analysis of the breaking loads, lateral displacements and deformations of the column of materials for different ways of preparing the surface of the column to be strengthened. The experimental phase of this work was based on testing of nine reinforced concrete columns, which are tested under flexural compression, with eccentricity of 60 mm. Two columns were used as reference columns, one with the original dimensions of the column and the other monolithic concreted in the thickness of a sin reinforced the others received a layer of 35 mm thick concrete selfcompacting in the compressed face. For preparation of the interchange between the two materials, it was proceeded with the scarification and the realization of grooves along this surface, where inserted connectors attached to transverse reinforcement of the columns, varying the position and quantity of the same. It can be concluded that not only quantity, but mainly the location of connectors used in the connection between the substrate and reinforcement, is essential for a good result of resistance and rupture mode. Must be observed a minimum spacing between the connectors strengthening to ensure a more monolithic unit, enabling a ductile rupture occurred as the reference column